STUDI DESKRIPTIF BENTUK PERTUNJUKKAN RABAB PASISIA PADA PESTA PERKAWINAN DI PEKONINA KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - Risa Febriani; Yensharti Yensharti; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2013)
Abstract This research aims to (1) describe and discover how the shape of the show At Pasisia party Rabab marriage in Pekonina Pauh Duo District in South Solok Regency, (2) This type of qualitative research methods a descriptive analysis. Main is the author's own Istrument, using the tools in the field such as writing instruments, cameras for recording and taking pictures. Data collection techniques through observation, interview and study library. Rabab pasisia performances in the form of the marriage festivities is shaped of joke performing arts night, serving a wide range of dendang-dendang pantun-pantun-shaped. The audience is the general public, show the relatives invited home masters and come see the show. Rabab pasisia Arts for local community serves as a means of entertainment and unifying community. Keyword : studi deskriptif, bentuk pertunjukkan, rabab pasisia, pesta perkawinan, pekonina